Pengaruh Rasio Keuangan CR, DER, GPM, dan TATO terhadap Kinerja Keuangan Emiten Migas di Bei Periode 2020–2024 - Dhita Nur Fadila; Sigit Puji Winarko; Andy Kurniawan (BADAN PENERBIT STIEPARI PRESS, 2025)
The background of this study stems from the fluctuating Return on Assets (ROA) observed among oil and gas companies in Indonesia. ROA is a key indicator of profitability that reflects a company’s efficiency in utilizing its assets to generate net income. As such, ROA plays a crucial role for investors in assessing the prospects and feasibility of investment. This study aims to analyze the influence of financial ratios on the financial performance of oil and gas companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. A quantitative approach was employed using panel data regression analysis with a random effects model. Secondary data were obtained from the annual financial statements of 16 selected oil and gas companies. The independent variables examined include the Current Ratio (CR) as an indicator of liquidity, the Debt to Equity Ratio (DER) as a measure of solvency, the Gross Profit Margin (GPM) as a profitability indicator, and the Total Asset Turnover (TATO) as an indicator of asset efficiency. The results of the study reveal that both GPM and TATO have a positive and significant influence on ROA. This suggests that higher gross profit margins and more efficient asset turnover are associated with improved profitability. In contrast, CR and DER do not show a significant impact on ROA. Collectively, the four financial ratios significantly affect ROA, as indicated by the F-test result with a significance value of 0.000 (< 0.05) and an R-squared value of 0.7127. This means that the model explains approximately 71.27% of the variation in ROA among the companies studied. In conclusion, the findings highlight that operational efficiency and the ability to generate gross profit are dominant factors in determining the financial success of oil and gas companies. Meanwhile, liquidity and capital structure appear to have less impact on profitability within the context of this study.